The pressures of getting it right: expertise and victims’ voices in the work of the Sierra Leone Truth and Reconciliation Commission (TRC) - Menzel, Anne (International journal of transitional justice)
This article contributes to scholarship on power, agency and ownership in professional transitional justice. It explores and details the relationship between ‘professional’ agency arising from recognized expertise and ‘unprofessional’ voices relaying lived experiences, concerns and needs. I approach this relationship via a microperspective on the work of the Sierra Leone Truth and Reconciliation Commission (2002-2004), specifically its work on women and sexual violence, which the commission was mandated to pay special attention to. Based on interviews and rich archival materials, I show how this work was driven by the notion that there was a right way of dealing with women and sexual violence. To avoid mistakes, commissioners and staff members demanded and relied on recognized expertise. This led to a marginalization of victims’ voices. I argue that, to some degree at least, such marginalization belongs to professional transitional justice and will persist despite improved victim participation.